Pembentukan Karakter Individu sebagai Agen Moral Kristiani menurut Wiliam C. Spohn - Simare Mare, Erni Dameria (Fakultas Teologi, Universitas Sanata Dharma, 2024)
The character building of Christian moral agents has an impact on the life of the faithful. Nowadays, there are various practices or behaviours that deviate from the proper teachings, such as bullying and ignoring the wrong social reality. Therefore, a character building is needed to reshape individuals to become moral agents by basing it on the formation of a distinctive character. The distinctive character can be exemplified through the figure of Jesus Christ as the prototype of Christian moral agent. This paper aims to present an approach from Wiliam Spohn as an offer for the formation of individual character as a Christian moral agent. The method used in this paper is a literature review of Wiliam Spohn's thoughts on virtue ethics and the life story of Jesus Christ in the New Testament as an approach that shapes the character of Christian moral agents. The result of this paper is that the contribution of Wiliam Spohn's thoughts can be one of the approaches that can be used to shape the character of Christian moral agents. By using the approach of virtue ethics and the life story of Jesus Christ in the New Testament from Wiliam Spohn can form a distinctive character for Christian moral agents.Abstrak Pembentukkan karakter agen moral kristiani memiliki daya dampak dalam tatanan kehidupan umat beriman. Di masa kini telah terjadi berbagai praktik ataupun perilaku yang menyimpang dari ajaran-ajaran yang semestinya, seperti tindakan bullying dan pembiaran pada realitas sosial yang salah. maka diperlukan sebuah pembentukan karakter untuk membentuk kembali pribadi-pribadi untuk menjadi agen moral dengan mendasarkannya pada pembentukan karakter yang khas. Karakter yang khas dapat diteladani lewat figur Yesus Kristus sebagai prototype agen moral kristiani. Tulisan ini hendak menyajikan sebuah pendekatan dari Wiliam Spohn sebagai sebuah tawaran untuk pembentukan karakter individu sebagai agen moral kristiani. Metode yang digunakan dalam tulisan ini adalah literatur review atas pemikiran Wiliam Spohn tentang etika keutamaan dan kisah hidup Yesus Kristus dalam Perjanjian Baru sebagai pendekatan yang membentuk karakter dari agen moral kristiani. Hasil dari tulisan ini adalah sumbangan pemikiran dari Wiliam Spohn dapat menjadi salah satu pendekatan yang dapat digunakan untuk membentuk karakter agen moral kristiani. Dengan menggunakan pendekatan etika keutamaan dan Kisah hidup Yesus Kristus dalam Perjanjian Baru dari Wiliam Spohn dapat membentuk karakter yang khas bagi agen-agen moral kristiani.